Centralidade para além do capital? uma discussão acerca dos conceitos de território e identidade em Venda Nova, Belo Horizonte - Gabriela de Faria Pinho (2021)
In this dissertation, the look at the urban is constructed from a lefebvrean perspective of the territory as work and product, and, if the metropolis is a starting point, the urban centrality is the object intended to deepen. From a case study of a descriptive and qualitative approach concerning the territory of Venda Nova, dealing at times with the centrality, and at other times with the region as a whole, it is understood that the alternation between scales is due to the impossibility of discussing the centrality unrelated to its periphery. Thus, assuming the existence of centralities both as a functional territory, guided by the capitalism production mode, by exchange value and exchange, existing as a product, and as symbolic territory, guided by appropriation, use value and use, resisting as work, we tried to answer the following question: Are there, in the centrality of Venda Nova, manifestations and appropriations that expand beyond exchange value, that is, beyond capital, towards use value? It is hypothesized that the centrality of Venda Nova would be a protagonist in the construction of a symbolic territory, shaped beyond capital, through appropriations based on use value through the construction of a territorial identity. However, this hypothesis has not been confirmed. The investigation showed that the centrality lost its role in the construction of symbolic territory. At the same time, this symbolic territory is built in other spaces and in other ways outside the centrality, more specifically, on its periphery and through the existence of multiple territorial identities built through urban movements. In this sense, the discussion expands on the notion of territorialization and the construction of territorial identities conceptualized by Haesbaert and Castells, with the objective of deepening the investigation of Venda Nova’s centrality, understanding its current conformation, the processes that occur in it, what type of centrality they generate and their influence on its periphery.